(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research is entitled Marketing Strategy Analysis of Ground Water Spinach Plants (Ipomoea reptans poir) (Case Study: Koa Madiyahi Farmer Group, Cobodoe Village, East Tidore District, Tidore Islands City, North Maluku Province). This thesis research will begin in July 2023 to August 2024. The research location consideration that the author took was that the research location could still be reached. This type of research is qualitative research with data collection using interview guidelines with informants who the author determines based on criteria. The results of this research show that the inhibiting factors for implementing marketing strategies for land kale plants are prolonged hot weather, lack of business capital; and the many pressures of competition with other sellers. So the solution given is to look for additional workers outside of farmer groups, provide sufficient supplies of water and fertilizer and strengthen business capital so that they can buy fertilizer and superior seeds. Apart from that, the Koa Madiyahi farmer group has implemented a marketing strategy that uses Product, Price, Promotion and Place indicators well so that it can increase profits from sales of land kale products.